Novejše dileme o dometu privilegija zoper samoobtožbo in prepovedi sojenja o isti stvari na primeru kršitev v zvezi z drogami - Hafner, Miha (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2025)
The authors examine two procedural dilemmas that arise in proceedings concerning drug-related offences (misdemeanour offences and criminal offences). The first part discusses the scope of the privilege against self-incrimination in situations where individuals are compelled to surrender objects upon request by state authorities. The second part addresses the problem of parallel punitive proceedings (misdemeanour and criminal proceedings) and, in this context, the scope of the prohibition of double jeopardy. The analysis focuses on recent developments in the case law of the European Court of Human Rights, the Court of Justice of the European Union, and domestic courts in relation to these questions. The authors demonstrate that the existing legislation does not provide detailed or precise guidance on how authorities should act when faced with such issues. Consequently, it has been left to the case law of European and domestic courts to give substance to these guarantees; however, in some respects, the answers remain ambiguous.
Keywords: kazniva dejanja; pravna negotovost; prekrški; prekrškovni postopek; prepoved ponovnega sojenja; prepovedane droge; privilegij zoper samoobtožbo; sodna praksa; ustavna jamstva